Police Strategy in Preventing Street Crime in Yogyakarta - Vicki Dwi Purnomo; Kelik Endro Suryono; Yustinus Bowo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Results that obtained in study this concluded that street crime is a rife that is committed by teenagers in the city of Yogyakarta. Acts of crime with sharp weapons, and bullying. In the last 3 months, crime cases have increased. Efforts have been made by Big City Resort Police ( Polrestabes) Yogyakarta to minimize and prevent crime This street is carried out by (a) Preentif namely conducting outreach or counselling to society including to school, (b) preventive ie do prevention with optimizing function Babinkamtibmas (NCO coach security And Order public) in wards, And (c) Repressive ie do prosecution direct if crime street happen.